(untitled) (Bangladesh Pharmaceutical Journal, 2016)
In this paper an effort has made to conduct and repot the computational study of geometry, IR spectrum and different molecular properties like Molecular Electrostatic Potential (MESP), Mulliken Charge Distribution, Global Reactivity Descriptors such as chemical hardness, softness, chemical potential, electronegativity, and electrophilicity index of acetanilide. All calculations were performed on Hartee-Fock (HF), Becke and 3-parameter, Lee-Yang-Parr (B3LYP) with 6-31G(d) and 6-31+G(d,p) basis sets. The calculated geometries (bond length, bond angle and dihedral angle) were in a good agreement with the experimental data for both level of theories and basis sets. In case of IR frequencies the scaled calculated frequencies agreed reasonably well with the experimental results. Bangladesh Pharmaceutical Journal 19(2): 170-178, 2016